Design and validation of a questionnaire of perception of the teacher's reform law N. º 29944 in public educational institutions of Metropolitan Lima - Viera Vilchez , Liliana (2025)
Educational reforms tend to impact educational actors and in particular affect teachers more (Sánchez-García et al., 2022 and Gutiérrez, 2022). Despite this, it does not suppress current demands, nor does it foster educational growth (García, 2017). In this context, the “Ley de Reforma Magisterial (LRM) N.° 29944” in Peru impacted the teacher, creating uncertainty and dissatisfaction (Gutiérrez, 2022 and Pantoja, 2022).  That said, the objective of the present study was to design and validate an instrument that measures the perception of Law No. 29944 by the 201 public education teachers of REI 10, UGEL 06 (Metropolitan Lima), comprised in the initial, primary and secondary levels; to which 30 items were applied. This questionnaire had a content validation of 0.881, according to Aiken V. Regarding the confirmatory factor analysis, the adequate adjustment indexes were: Xs2/gl = 1.682, SRMR = 0.052, RMSEA = 0.0058, CFI = 0.915, TLI = 0.906. To conclude, the reliability, according to Cronbach's Alpha, showed an excellent level of 0.949. For this reason, this questionnaire is valid and effective to know the perception that teachers have of “La Reforma Magisterial” in public educational institutions and thus improve their working conditions.